Rush. The complete season 1 [videorecording (DVD)]. - Ellis, Tom, 1978-; Tate, Larenz; Habel, Sarah; Gonzalez, Rick, 1979- (Twentieth Century Fox Film Corporation, 2014)
Not only does Dr. William Rush's thriving L.A.-based medical practice include celebrities, moguls and gangsters, it's a completely private affair. As a highly skilled doctor who makes house calls to some of the most dangerous locations in the city, he can name his price, and its cash only.